Adsorption of Inorganic As(III) from Aqueous Solutions by Iron-Manganese Oxide - Koju, Rashmi; Dhakal, Agni; Gwachha, Sushila; Joshi, Dev Raj; Joshi, Tista Prasai; Shrestha, Sujen Man (Scientific World, 2020)
Arsenic contamination in water is well noted public health issue in Nepal and elsewhere. Adsorbents are important chemical means to purify the arsenic contaminated water. In this study the adsorption of As(III) on iron manganese oxide has been investigated as a function of different parameters. Herein, two iron based adsorbents, iron-manganese oxide-1 (Fe-Mn oxide-1) and iron-manganese oxide-2 (Fe-Mn oxide-2) were prepared by oxidation and co-precipitation methods. Adsorbents were characterized by powder X-ray diffraction (XRD) and scanning electron microscope (SEM). Within 4 hours of reaction time, 90% of the arsenic was removed by both Fe-Mn oxides and removal efficiency of the Fe-Mn oxide-1 was obtained higher than that of Fe-Mn oxide-2. Pseudo-second order model was well fitted to describe adsorption kinetic (R2 =0.99) for both adsorbents. Removal efficiency of the absorbents decreased with increase in the pH value and increased with increase in the concentration of adsorbent in the suspension. Based on the result, the synthesized Fe-Mn oxides have significant potential applications in the inorganic arsenic treatment in the water.